Impact of including Korean randomized controlled trials in Cochrane reviews of acupuncture. - Kun Hyung Kim (Public Library of Science (PLoS), 2012)
Objective Acupuncture is commonly practiced in Korea and is regularly evaluated in clinical trials. Although many Cochrane reviews of acupuncture include searches of both English and Chinese databases, there is no information on the value of searching Korean databases. This study aimed to investigate the impact of searching Korean databases and journals for trials eligible for inclusion in existing Cochrane acupuncture reviews. Methods We searched 12 Korean databases and seven Korean journals to identify randomised trials meeting the inclusion criteria for acupuncture reviews in the Cochrane Database of Systematic Reviews. We compared risk of bias assessments of the Korean trials with the trials included in the Cochrane acupuncture reviews. Where possible, we added data from the Korean trials to the existing meta-analyses in the relevant Cochrane review and conducted sensitivity analyses to test the robustness of the results. Results Sixteen Korean trials (742 participants) met the inclusion criteria for eight Cochrane acupuncture reviews (125 trials; 13,041 participants). Inclusion of the Korean trials provided data for 20% of existing meta-analyses (24 out of 120). Inclusion of the Korean trials did not change the direction of effect in any of the existing meta-analyses. The effect size and heterogeneity remained mostly unchanged. In only one meta-analysis did the significance change. Compared to the studies included in the Cochrane acupuncture reviews, the risk of bias in the Korean trials was higher in terms of outcome assessor blinding and allocation concealment. Conclusions Many Korean studies contributed additional data to the existing meta-analyses in Cochrane acupuncture reviews. Although inclusion of these studies did not alter the results of the meta-analyses, comprehensive searches of the literature are important to avoid potential language bias. The identification and inclusion of eligible Korean trials should be considered for reviews of acupuncture.